Total heat loss in broilers fed with different lipid sources - Álvarez, Edgar Alejandro Oviedo (2022)
To meet the growing demand for poultry products, many producers have decided to increase the density of animals per square meter. This, coupled with global warming, creates a severe problem for the poultry industry, as it is common to observe birds moving away from the thermal comfort zone. Therefore, the objective of this study was to evaluate the effect of three lipid sources and three levels of inclusion in broiler diets on sensible heat loss. Three hundred twenty-four female broilers from the Ross 308 line were housed in cages in an open house and distributed into nine different treatments. The body surface temperature was observed with an infrared thermography camera. Heat loss was analyzed by radiation, and convection was calculated by equations at weeks three, four, and six of broiler life, considering the importance of measuring and analyzing the following variables: wind speed, bird weight, bird area, ambient temperature, and relative humidity, among others. The treatments had no significant effect on Qt; however, the inclusion of palm oil, chicken oil at 3%, and sacha inchi oil at 9% can be an alternative in broiler chicken feed since they tend to reduce Qt at day 42 of life.